A Study On The Decorations Of Ilkhani Era: A Case Study Of Dome Of Soltaniyeh - Sobouti, Hooman; Ghasemi, Ali (The Turkish Online Journal of Design Art and Communication, 2016)
The Mongols, in the late sixth and early seventh century AH, invaded their surrounding territories and occupied large parts of the civilized world at that time, constituting the largest contiguous empire in human history in terms of land area. The Mongols' devastating attack on Iran took place in the early seventh century AH and resulted in the loss of many of our cultural heritage. Mongol rule and creation of Ilkhani family in Iran and Central Asia as well as the acceptance of Islam at the end of their rule and also the use of Iranian artists and arts would end in flourishing of architecture and its affiliates. Undoubtedly one of the most important surviving monuments of that period is the Dome of Soltaniyeh decorated by unmatched paintings on plaster, tiling, lattice brickwork, plaster and brick Mogharnas, plasters on fabric and inscriptions embellished with Quranic verses and traditional content. The current study which is a analytical/descriptive study, aimed at investigation of decorations of Ilkhaniera and its unmatched masterpiece of the Dome of Soltaniyieh.
Keywords: Ilkhani; decorations; Dome of Soltaniyeh